33 Influence of ethnicity on outcomes in primary percutaneous coronary intervention for ST-elevation myocardial infarction. (24th April 2016) - Krishnamurthy, Arvindra; Somers, Kathryn; Burton-Wood, Natalie; Anderson, Michelle; Harland, Charlotte; Keeble, Claire; Mclenachan, James M; Blaxill, Jonathan M; Malkin, Christopher J; Blackman, Daniel J; Wheatcroft, Stephen B; Greenwood, John P
Abstract : Introduction: Clinical outcomes following Primary PCI (PPCI) for ST Elevation Myocardial Infarction (STEMI) continue to improve with the evolution of techniques and pharmacotherapy. The West Yorkshire PPCI study was set up to allow identification of clinical and procedural variables that could impact on outcomes following PPCI. We analysed the influence of ethnicity on major adverse cardiovascular events (MACE) and mortality following PPCI. Methods: Retrospective analysis of 3049 consecutive patients undergoing PPCI for STEMI between 01–01–2009 and 31–12–2011 at Leeds General Infirmary. Clinical data up to a minimum of 12m following PPCI were collected. Analyses of total mortality and MACE of white patients (n = 2570, mean 64 ± 13yrs) and Asian patients (n = 297, mean 58 ± 14yrs) were performed with Cox proportional hazards models. MACE was defined as death, MI and unplanned revascularisation. Results: There was no statistically significant difference in outcomes between the ethnic groups (Figure 1 ). Discussion and conclusion: This large retrospective study has revealed no statistically significant difference in mortality or MACE between Asian and white patients following PPCI.